2014
DOI: 10.1016/j.slsci.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between chronotype and quality of sleep in medical students at the Federal University of Paraiba, Brazil

Abstract: ObjectiveThe aim of this study was to identify chronotypes of medical students at the Federal University of Paraíba (UFPB) and its relationship to quality of sleep, daytime sleepiness, age, sex and season of birth.MethodsThe final sample consisted of 221 students, assessed by four questionnaires: demographic questionnaire, Morningness–Eveningness Questionnaire (MEQ), Pittsburgh Sleep Quality lndex (PSQI) and Epworth Sleepiness Scale (ESS).ResultsThere was a statistically significant difference between groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
5
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 44 publications
(61 reference statements)
13
64
5
6
Order By: Relevance
“…The sleep duration of students in our study was short; this is in line with the results of previous studies, which reported that the sleep duration of Japanese university students was shorter than those of university students in other countries [1]. In the present study, the prevalence of evening-type individuals (16%) was lower than that of previous studies, which reported results that ranged from 20 to 35% [41][42][43]. Multiple imputation by chained equations with a five-imputation dataset was performed for missing data…”
Section: Insomnia Insufficient Sleep and Delayed Sleep-wake Phase Insupporting
confidence: 90%
“…The sleep duration of students in our study was short; this is in line with the results of previous studies, which reported that the sleep duration of Japanese university students was shorter than those of university students in other countries [1]. In the present study, the prevalence of evening-type individuals (16%) was lower than that of previous studies, which reported results that ranged from 20 to 35% [41][42][43]. Multiple imputation by chained equations with a five-imputation dataset was performed for missing data…”
Section: Insomnia Insufficient Sleep and Delayed Sleep-wake Phase Insupporting
confidence: 90%
“…Last part of SDQ, Epworth sleepiness score consists of 8 items about probability of sleeping in different situations, which ranges from 0 (never) to 3 (high chance of dozing). The total score of ESS considered in a scale of 0-24, so final grade class has been calculated as 3-9 (Normal), 10-13 (mild), 14-19 (moderate) and 20-24 (severe sleepiness) 20,21 The validity of the questionnaire has been established in previous studies. 22 In this study, the internal reliability of Cronbach Alpha was 0.86.…”
Section: Methodsmentioning
confidence: 99%
“…They typically wake up later than the morning chronotype people ("larks"). Evening chronotype people have poorer sleep quality and lower professional performance [65], higher mortality and reduced longevity [66].…”
Section: Too Much Rem Sleepmentioning
confidence: 99%